2012
DOI: 10.1111/j.1741-4369.2012.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

“…If we were cavemen we'd be fine”: Facebook as a catalyst for critical literacy learning by dyslexic sixth‐form students

Abstract: This article is derived from a study of the use of Facebook as an educational resource by five dyslexic students at a sixth form college in north‐west England. Through a project in which teacher‐researcher and student‐participants co‐constructed a group Facebook page about the students’ scaffolded research into dyslexia, the study examined the educational affordances of a digitally mediated social network. An innovative, flexible, experiential methodology combining action research and case study with an ethnog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
0
22
1
4
Order By: Relevance
“…Through making visible interwoven strands of communication and learning (Hulme, 2009;Facer, 2011) the methods enabled the study to meet its aims, by showing that Facebook provided the participants with an arena for active, critical learning about and through literacy (Author, 2012). The data showed that the students were highly motivated to learn through literacy, contrary to what much of the dyslexia discourse suggests.…”
Section: Discussioncontrasting
confidence: 45%
“…Through making visible interwoven strands of communication and learning (Hulme, 2009;Facer, 2011) the methods enabled the study to meet its aims, by showing that Facebook provided the participants with an arena for active, critical learning about and through literacy (Author, 2012). The data showed that the students were highly motivated to learn through literacy, contrary to what much of the dyslexia discourse suggests.…”
Section: Discussioncontrasting
confidence: 45%
“…The United States was the most well‐represented location with six (Bruce, ; Englert et al, ; Hutinger et al, ; Orr, ; Rao et al, ; Sylvester and Greenridge, ). The next most frequent site was the United Kingdom with four (Barden, ; Faux, ; Flewitt et al, ; Lacey et al, ), followed by Australia (Elliot, ; Pickering, ). One study (O'Rourke et al, ) was a collaborative effort between researchers and teachers in Northern Ireland and the United States, and one (Snoddon, ) was conducted in Canada.…”
Section: Resultsmentioning
confidence: 99%
“…Elliot () argued that Minecraft and other video game‐based curricula empower disadvantaged learners (echoing Gee []). In a similar vein, Barden () aimed to document the ways Facebook participation could motivate students with dyslexia to write and read more. Sylvester and Greenridge () used digital storytelling to enhance the learning of struggling writers, Snoddon () focused on the development of literacy skills and enhancement of literacy identities of deaf children, Hutinger et al () on enhancing early literacy development with technology and Englert et al () on the ways technology‐enhanced scaffolds could help children become better writers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many have considered how learners might use new media to take increasing control of their lives and engage critically with the world around them (Bigum 2002;Jenkins 2006). Examples of uses in education include computer gaming (Apperely and Walsh 2012), virtual worlds (Merchant 2010), multimedia composition (Burn 2009) and social networking (Barden 2012). Such opportunities however can present challenges to practitioners as they may not sit easily alongside other priorities and practices.…”
mentioning
confidence: 99%